Molecular diversity and genetic structure of Saccharum complex accessions as revealed by TRAP markers - Souza, Carolina Medeiros de (Universidade Federal de São Carlos, 2019)
Sugarcane has great economic importance for Brazil and for the world as a raw material, mainly for the production of sugar and ethanol. Conventional breeding is one of those responsible for raising productivity levels, however, the genetic gains for the characteristics of economic interest have been decreasing. The use of molecular markers to evaluate the genetic variability in germplasm banks can contribute to the genetic improvement in the selection of parents for crossing and consequent obtaining of superior progenies. Molecular markers of the TRAP (Target Region Amplification Polymorphism) type are anchored in functional genes that have the known sequence allowing to evaluate the variability in this region of the genome. Thus, the objective of this work was to evaluate the diversity and genetic structure of Saccharum complex accessions that make up the Brazilian Panel of Sugarcane Genotypes (BPSG) using TRAP markers anchored in sucrose and lignin metabolism genes. BPSG is installed in the field at the Agricultural Sciences Center (CCA) of the Federal University of São Carlos (UFSCar). The DNA of the accessions was extracted from the fresh meristem cylinder and the amplifications of the TRAP markers for sucrose and lignin were performed, respectively. The detection of amplified products was performed after electrophoresis in 6% polyacrylamide gel with silver nitrate staining. The obtained fragments were classified as "1" for presence and "0" for absence. From the total set of fragments obtained and using software R were estimated: i) genetic distance through the Jaccard coefficient; ii) PIC (Polymorphic Information Content) and DP (Discriminatory Power); iii) PCA (Principal Components Analysis) and; iv) dendrogram through the Neighbor-Joining method. In addition, AMOVA (analysis of molecular variance) was also performed using GenAIEx software and population structure analysis using STRUCTURE software. TRAP markers generated a total of 595 fragments of which 584 (98.15%) were polymorphic. The mean genetic distance between the accessions was 0.3, with the shortest distance between accessions RB721012 and CB40-13 (0.10), and the longest distance between accessions SES205A and CAIANA FITA (0.62). The PIC ranged from 0.99 (F4 + Arbi1-S) to 0.95 (SuPS + Arbi2 and SuPS + Arbi3). The DP ranged from 0.95 (F4 + Arbi1-S) to 1 (StSy + Arbi3). The first and second main components explained 12.4% and 5.4% of the total variability expressed between the accessions, respectively. For AMOVA, the accessions were separated into three groups: i) ancestral (A), composed of accessions of Saccharum spp. and the genus Erianthus; ii) Brazilian breedings (BB), containing the accessions of the Brazilian breeding programs; and iii) foreign hybrids (FH), composed of accessions originated from other countries. When AMOVA was performed between groups A and BB, the fixation index was 0.14 (14% of the total variation between the two groups), while the indexes between the BB and FH groups and between A and FH were corresponding to 0.03 and 0.05, respectively. The analysis of population structure showed the formation of two groups: the first composed by the accessions of group A - and the second containing the accessions of groups BB and FH. In the dendrogram, the accessions were divided in 3 clades, and clade 1 was composed mainly by accessions of group A and FH, while clades 2 and 3 by accessions of group BB. Thus, through TRAP markers associated with sucrose and lignin genes, it was possible to estimate the genetic diversity of BPSG and population structure. The data obtained in this work can be explored in the future for studies of association and help breeding programs in the choice of parents and obtaining of superior progenies.
Diversidade molecular e estrutura genética de acessos do complexo Saccharum revelados por marcadores TRAP
Keywords: Distância genética; Marcadores moleculares; Cana-de-açúcar; Sacarose; Lignina; Genetic distance; Molecular markers; Sugarcane; Sucrose; Lignin; CIENCIAS AGRARIAS